Living standards shape individual attitudes on genetically modified food around the world. (January 2022) - Levi, Sebastian
Highlights: Public opinion on genetically modified food most positive in developing countries. Machine learning analysis of consumer attitudes on GMO food across 142 countries. Attitudes on GM crops and livestock driven by economic development and hunger. Economic development moderates how demographic traits predict individual attitudes. Effect of gender, education, and urbanicity varies across country groups. Abstract: Agricultural biotechnology may help to sustainably intensify food production, but negative public opinion hinders the deployment of genetically modified crops and livestock. Previous research shows negative consumer attitudes in Europe and North America to be primarily driven by limited trust and religiosity, but public opinion elsewhere remains underexplored. Here, analyzing individual attitudes across 142 countries with conventional statistics and machine learning, I find support for genetically modified food in low-income countries to be 19 percentage points higher than in affluent countries. Globally, individual attitudes are primarily determined by living standard, agricultural output, and prevalence of undernourishment (p < 0.001). Country income levels also moderate how demographic characteristics predict attitudes on bioengineered food. Highly educated urban men are most optimistic about agricultural biotechnology in high-income countries, while women, individuals living in rural areas, and those with little education are the most hopeful demographic in low-income countries. The results indicate that individual views are largely determined by the societal benefits expected from agricultural biotechnology and suggest that the conditions for further deregulation of genetically modified food are most favorable in low-income countries.